Tugas dan Sifat Politik Hukum terhadap Sistem Hukum di Indonesia - Vedita Akbar; Nada Prima Dirkareshza; Taufiqurrohman Syahuri (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Legal politics plays a role in determining the direction of legal policy that must be taken by the government to achieve certain goals. Legal politics is a very important component, one of which is the implementation of existing laws in the country and every policy taken by the government reflects existing political dynamics and the interests of certain groups, thereby affecting the integrity and justice of the existing legal system. The purpose of writing this article is to research further on how the duties and objectives of legal politics are applied to the Indonesian legal system and whether the application of the nature of legal politics is appropriate to the Indonesian legal system. The method used is normative juridical with a statutory and conceptual approach. Legal politics in Indonesia is normative, dynamic, adaptive, pragmatic, progressive, and functions as a tool of social control. However, implementation is often hampered by political interests and lack of consistent implementation. Therefore, there is a need for regular regulatory evaluation, increased transparency of law enforcement, and public participation to create a more responsive and fair legal system.